PEMANFAATAN TEKNOLOGI DIGITAL DALAM EVALUASI PEMBELAJARAN PAI - Nida Fadhila Safitri; Anggun Setiani; Zahwa Ardhinia Naisa; Rahma Ihda Fatimah Azzahro; Alda Mafrikha Fauziah; Ceren Desta Joina; Ridho Riyadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the use of digital technology in the evaluation of Islamic Religious Education (PAI) learning, its impact on the effectiveness of assessments, the challenges of implementation, and strategies for optimization. The method used is a literature study (library research) by analyzing various relevant scientific literature. The results of the study show that the use of digital platforms, such as Google Forms, Quizizz, Kahoot, GradeScope, and Learning Management Systems (LMS), can improve the efficiency, objectivity, and speed of the evaluation process. In addition, digital technology encourages active student participation through more interactive assessments, enhances learning outcomes, and supports more comprehensive assessment of cognitive, affective, and psychomotor aspects. However, its implementation still faces various obstacles, including limited teacher digital competence, uneven technology infrastructure, and unstable internet access. and the low readiness of institutions in supporting digital transformation. Therefore, an optimization strategy is needed through improving teachers' digital literacy, providing adequate facilities and infrastructure, developing innovative technology-based evaluation instruments, implementing blended assessments, and supporting sustainable policies. With the implementation of this strategy, digital technology is expected to make Islamic Education learning evaluations more effective, efficient, objective, authentic, and aligned with the demands of 21st-century education without disregarding Islamic values.